Suicide in patients suffering from late-life anxiety disorders; a comparison with younger patients. (11th February 2015) - Oude Voshaar, R. C.; van der Veen, D. C.; Kapur, N.; Hunt, I.; Williams, A.; Pachana, N. A.
ABSTRACT: Background: Anxiety disorders are assumed to increase suicide risk, although confounding by comorbid psychiatric disorders may be one explanation. This study describes the characteristics of older patients with an anxiety disorder who died by suicide in comparison to younger patients. Method: A 15-year national clinical survey of all suicides in the UK ( n = 25, 128). Among the 4, 481 older patients who died by suicide (≥ 60 years), 209 (4.7%) suffered from a primary anxiety disorder, and 533 (11.9%) from a comorbid anxiety disorder. Characteristics of older ( n = 209) and younger ( n = 773) patients with a primary anxiety disorder were compared by logistic regression adjusted for sex and living arrangement. Results: Compared to younger patients, older patients with a primary anxiety disorder were more often males and more often lived alone. Although 60% of older patients had a history of psychiatric admissions and 50% of deliberate self-harm, a history of self-harm, violence, and substance misuse was significantly less frequent compared to younger patients, whereas physical health problems and comorbid depressive illness were more common. Older patients were prescribed significantly more psychotropic drugs and received less psychotherapy compared to younger patients. Conclusion: Anxiety disorders are involved in one of every six older patients who died by suicide. Characteristics among patients who died by suicide show severe psychopathology, with a more prominent role for physical decline and social isolation compared to their younger counterparts. Moreover, treatment was less optimal in the elderly, suggesting ageism. These results shed light on the phenomenon of suicide in late-life anxiety disorder and suggest areas where prevention efforts might be focused.